Implementasi Teknologi Internet of Things (IoT) pada Sistem Keamanan Loker dengan Verifikasi Biometrik - Sadali, Muhamad; mahpuz; Arifin, Muhammad; Wasil, Muhammad (Jurnal PRINTER: Jurnal Pengembangan Rekayasa Informatika dan Komputer, 2025)
In the increasingly advanced digital era, the need for a sophisticated and integrated security system is very important, especially to protect valuables in lockers. Conventional lockers are often vulnerable to theft or unauthorized access due to the lack of security systems. Therefore, fingerprint authentication technology, which is unique to each individual, is an effective solution to improve locker security. This system ensures that only users who have registered fingerprints can open the locker. In addition, with the support of Internet of Things (IoT) technology, this system allows remote monitoring and control, providing flexibility and ease of use. This study develops a locker security system based on fingerprint authentication integrated with IoT, with the aim of reducing the risk of theft and unauthorized access. The test results show that out of 7 fingerprints tested, there was 1 fingerprint that was not recognized by the system on the first try, even though the fingerprint had been registered. This failure identifies a problem in reading the fingerprint ID, so overall it can be concluded that the system's accuracy level reaches 90%.